Decision support system for the best employee performance appraisal using the web-based exponential comparison method (ecm) at bank mandiri palembang - Gustriani Purwanti; Winoto Chandra (Jurnal Mantik, 2023)
In this current condition, technology is developing very rapidly, so that all companies use computers for data processing to produce the accurate data. However, data processing using a computer only is not enough, so it must use a system that can help the performance of the data processor. One of the application required here is an application in giving rewards to employees at Bank Mandiri Palembang as the work productivity, employee behavior, and employee attitudes. This system is very helpful for Bank Mandiri Palembang in the process of giving rewards to bank employees, so that the reward process does not experience errors and takes quite a long time because the employee reward application uses the exponential comparison method. Thus, all data entered will be processed by this application with using the exponential method so that the reward data can process quickly and produces the accurate data. This calculation process is based on criteria that have been determined by Bank Mandiri Palembang for employees who receive rewards.